PEMODELAN KENYAMANAN JALUR SEPEDA KAMPUS UNIVERSITAS GADJAH MADA MEMANFAATKAN FOTO UDARA FORMAT KECIL - , FILIAL NUR HIDAYAT, Barandi Sapta Widartono, S.Si., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Unavailability of information about the bike lane convenience in Gadjah Mada University campus is the background of this research. On the other hand the availability of small format aerial photography (SFAP) can assist in providing information about the parameters that affect the convenience of the bike lane. Based on these facts, this research goal is to determine the interpretation accuracy of parameters of the bike lane convenient that can be acquired with SFAP which then generates a map of bike lane convenient. This research reviewing small format aerial photography capabilities in providing information on the six parameters that influence the cycling convenient. Four of which can be extracted by SFAP using visual interpretation method i.e. the presence of vegetation shade with 98.0392% accuracy of interpretation, the presence of a bike lanes marker on second with 81.3725% accuracy of interpretation, the existence of side barriers in the third with 68,6725% accuracy of interpretation, and the density of traffic on the last thread with 54.9020% accuracy interpretation. While the other parameters, namely bike lanes relief and the relative position of a motor vehicle is extracted through a field survey. Once the model is developed, itâs known that there is 32 bike lanes have very low levels of convenient, 43 bike lanes have low levels of convenient, 44 bike lanes have middle levels of convenient, 54 bike lanes have high levels of convenient, and 31 bike lanes have very high levels of convenient. This data is then visualized in map to be easily understood by the map user.